Development of Online Video-Based Learning Media as an Alternative for Accounting Education, A Conceptual - Nurwendari, Weny; Yusrizal, Yusrizal; Musnadi, Said; Yunus, Muhammad (Journal of Education Culture and Society, 2025)
Aim. This literature review explores the development of video-based learning media as an alternative to accounting learning through online communication. In the digital era, the use of technology in education is becoming increasingly important, especially when face-to-face learning is not possible. Video-based learning media offer greater flexibility and accessibility, allowing students to learn at their own pace and time. Methods. This study method involves the analysis of various academic sources about the use of video and technology in accounting learning. Results. The results show that video-based learning can improve concept understanding, student engagement, and learning outcomes. Learning videos also allow for a more interactive and engaging presentation of material that can be accessed anytime. Challenges in implementation include the need for technological skills and the quality of infrastructure. Providing sufficient training and technical support and designing videos that align with the curriculum is crucial to address these challenges. Conclusion. This study concludes that online video-based learning media is a viable and effective alternative for accounting education when executed with careful planning and implementation.